KUALITAS PELAYANAN PADA SEKOLAH DASAR NEGERI INPRES 6/75 MADIDIR KOTA BITUNG - KURAMA, DIANA; LENGKONG, FLORENCE; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
Schools have a role in providing quality services to the community where the role of the school against aÂ community in it is to educate the nation's life community intelligence can be developed through formal andnon-formal education. Schools must be able to apply their roles to the community so that the communitygets the effect of satisfaction on the services provided by the school, but the lack of a maximum level ofservice quality in schools is something that needs to be considered as in providing learning to students isnot done optimally, Teacher Behavior who are less professional in serving the community and theperformance of the teaching staff/teacher is not yet maximal in teaching students at school. The purposeof the study was to find out how the quality of service in Elementary Schools (SD) Inpres 6/75 MadidirBitung CityThis research was conducted using a qualitative approach. Data Analysis Techniques In this studyqualitative analysis of Miles and Huberman was usedThe results showed that the quality of service at the Inpres 6/75 Madidir State Primary School was classifiedas good in terms of existing service devices both teachers and staff at the school had done their job well sothat the customers, students, and lever students were satisfied with the service. That in carrying out theirduties, all service devices, both teachers and staff, in the Elementary School of Inpres 6/75 Madidir havefollowed the applicable rules. all staff in providing customer services so that they are satisfied with the waythe service is carried out and by applying the nature of courtesy and friendliness so all work can becompleted properly within the allotted timeKeywords: Service Quality, Elementary School